Interrelating differences in structural and functional connectivity in the older adult's brain. Issue 18 (2nd August 2022) - Stumme, Johanna; Krämer, Camilla; Miller, Tatiana; Schreiber, Jan; Caspers, Svenja; Jockwitz, Christiane
Abstract: In the normal aging process, the functional connectome restructures and shows a shift from more segregated to more integrated brain networks, which manifests itself in highly different cognitive performances in older adults. Underpinnings of this reorganization are not fully understood, but may be related to age‐related differences in structural connectivity, the underlying scaffold for information exchange between regions. The structure–function relationship might be a promising factor to understand the neurobiological sources of interindividual cognitive variability, but remain unclear in older adults. Here, we used diffusion weighted and resting‐state functional magnetic resonance imaging as well as cognitive performance data of 573 older subjects from the 1000BRAINS cohort (55–85 years, 287 males) and performed a partial least square regression on 400 regional functional and structural connectivity (FC and SC, respectively) estimates comprising seven resting‐state networks. Our aim was to identify FC and SC patterns that are, together with cognitive performance, characteristic of the older adults aging process. Results revealed three different aging profiles prevalent in older adults. FC was found to behave differently depending on the severity of age‐related SC deteriorations. A functionally highly interconnected system is associated with a structural connectome that shows only minor age‐related decreases. Because this connectivity profile was associated with the most severe age‐related cognitive decline, a more interconnected FC system in older adults points to a process of dedifferentiation. Thus, functional network integration appears to increase primarily when SC begins to decline, but this does not appear to mitigate the decline in cognitive performance. Abstract : Aging is accompanied by a functional reorganization which manifests itself in cognitive performance differences, especially in older adults. Sources of functional reorganization are not fully understood but have been associated with structural connectivity differences. Based on a large cohort of older adults we show that functional connectivity behaves in relation to age‐related structural connectivity differences and further, that a functional dedifferentiated system, associated with minor structural connectivity decreases, is nonbeneficial in terms of cognitive performance maintenance.